An INTEGRATIVE MODEL FOR RESOLVING LAND TENURE CONFLICTS IN PROTECTED FOREST AREAS: MODEL INTEGRATIF PENYELESAIAN KONFLIK PENGUASAAN TANAH DALAM KAWASAN HUTAN LINDUNG - A.P, Aulia Oktraizka Vivi Puspita Sari; Wahanisa, Rofi (Pusat Studi Konstitusi dan Perundang-undangan, 2025)
Land tenure conflicts in protected forest areas are one of the most complex agrarian issues that remain unresolved to this day. This phenomenon occurs due to the imbalance between the state's legal claims through forestry policies and the socio-economic realities of communities that have long lived and worked on land within forest areas. One concrete case is found in the Protected Forest Area Register 45B Pekon Sukapura, West Lampung Regency. The community in this area faces legal uncertainty, criminalisation, and limited economic and social access due to the lack of legal recognition of their existence. This study aims to formulate an integrative conflict resolution model, taking into account the legal, social, and ecological dimensions in a holistic and contextual manner. This study uses a legal-sociological approach with descriptive-qualitative methods. Data was collected through in-depth interviews with the head of the land office, village chief, traditional leaders, and community members, as well as through document analysis of regulations, institutional reports, and academic studies. Analysis was conducted thematically, linking findings to Rawls' theory of social justice and Chambliss & Seidman's theory of how law works. The results of the study indicate that conflict resolution in the Register 45B area requires an integrative policy model, namely a model that combines the legalisation of community rights through TORA-based agrarian reform mechanisms, active community participation to achieve social justice, and efforts to maintain the ecological protection function of the area. This integrative model is expected to serve as an applicable policy framework for resolving agrarian conflicts in protected forest areas in a fair, sustainable, and inclusive manner.